Happiness, altruism and the Prius effect: How do they influence consumer attitudes towards environmentally responsible clothing?. Issue 1 (13th March 2017) - Reimers, Vaughan; Magnuson, Bryce; Chao, Fred
Abstract : Purpose: Academic research and consumer polls often report strong consumer support for environmentally responsible products (ERPs), and yet the proportion of sales they account for is often comparatively small. The purpose of this paper is to address one of the purported reasons behind this "attitude-behaviour gap" by measuring the influence of six relatively untested factors on consumer attitudes towards environmentally responsible clothing (ERC). Design/methodology/approach: This study employed a consumer household sample. It also used a quantitative survey approach to collect its data and structural equation modelling to analyse it. Findings: Of the six factors, four were found to have a significant influence on consumer attitudes: altruism, status enhancement, perceived consumer effectiveness (PCE) and happiness. Originality/value: Altruism, environmental concern, PCE and self-identity have consistently featured in other environmental contexts, but less so in the specific context of ERC. Happiness and status enhancement have yet to appear in any study relating to the purchase of ERPs.